Основні аспекти туристичної галузі України в період Євроінтеграції - Гальцова, О. Л.; Galtsova, Olga; Юрченко, Н. І.; Yurchenko, Nataliia (Класичний приватний університет, 2019)
У статті висвітлено основі аспекти туристичної галузі в період євроінтеграції. А також проаналізовано туризм як перспективний сектор євроінтеграційних процесів. Досліджено основні фактори, що стримують розвиток туристичної сфери в Україні. Туризм відіграє важливу роль у стимулюванні економічного розвитку не тільки туристичної галузі, але й суміжних галузей, а також інших галузей економіки. Зростання туризму позитивно впливає на споживчий попит, рівень валютних надходжень, а також на зайнятість населення. Роль туризму для розвитку національної економіки важко переоцінити. Туристична галузь має об’єктивні передумови свого розвитку, що склалися на підставі історичних, географічних, культурних та економічних чинників. Туристична індустрія почала приносити високі прибутки країнам, які її розвивають, а також країнам Європейського союзу. Сьогодні туристичний ринок набуває високо конкурентного середовища, в якому кожна країна намагається стати першою у просуванні туристичного товару. Прибутки від туристичної галузі з кожним роком займають все більші показники у бюджетах країн світу. Саме тому розвиток туристичної діяльності в Україні є важливим чинником в умовах євроінтеграції. The article highlights the aspects of the tourism industry in the period of European integration. Tourism has also been analyzed as a promising sector of European integration processes. The main factors limiting the development of tourism in Ukraine are investigated. Tourism plays an important role in stimulating the economic development of not only the tourism industry but also related industries as well as other sectors of the economy. Increasing tourism has a positive effect on consumer demand, foreign exchange earnings, and employment. The role of tourism in the development of the national economy is difficult to overestimate. The tourism industry has objective prerequisites for its development based on historical, geographical, cultural and economic factors. The tourism industry has started to generate high profits for developing countries and the European Union. Today, the tourism market is becoming a highly competitive environment in which each country tries to become the first to promote the tourism product. The profits from the tourism industry are increasing every year in the budgets of the countries of the world. That is why the development of tourist activity in Ukraine is an important factor in the context of European integration. The European Union is a complex and unique phenomenon in the modern system of international relations. In historical and political-institutional terms, European integration is defined as a process of gradual delegation of national powers to the pan-European level, which led to the formation of its distinctive political system. This model is characterized by a culture of dialogue, as well as compromise, grouping of elements of supranational integration and international cooperation, the formation of horizontal transnational networks and interaction and decision-making. The EU is a major factor in the modern governance and policy-making processes at European level. To date, the reform of economic processes in Ukraine, which are rapidly occurring primarily due to
Main aspects of the tourist industry of Ukraine in the European integration period
Keywords: туризм; tourism; туристична індустрія; tourism industry; туристичний кластер; tourism cluster; євроінтеграція; European integration; євроінтеграційні процеси; European integration processes